Characterization of an Epstein-Barr virus-induced thymidine kinase. - de Turenne-Tessier, M (1986)
Previous work from our laboratory suggested that the selective inhibition of Epstein-Barr virus (EBV) replication by 1-beta-D-arabinofuranosylthymine in human lymphoid cell lines involved the induction of a new thymidine kinase (TK) able to phosphorylate the thymidine analog. We further characterized this enzyme induced in various EBV-positive cell lines after viral genome activation with a combination of sodium butyrate and 12-O-tetradecanoylphorbol-13-acetate. The following results confirmed the existence of an EBV-specific deoxypyrimidine kinase: induction of EBV-related TK was connected with the appearance of viral early antigens in EBV-carrying cells; unexpected behaviors of the enzyme activity upon different fractionating treatments led to the conclusion that EBV-induced TK was extracted as a complex molecular form, larger than other known cellular or viral isozymes; enzymatic properties distinguished EBV-induced TK from host lymphoid cell isozymes but made it resemble other herpesvirus-specific deoxypyrimidine kinases, i.e., by partial inhibition by dTTP or ammonium sulfate, insensitiveness to dCTP, and nonstringent specificity for normal TK substrates. Genetic evidence is required to definitively ensure that EBV-specific TK actually is virus coded in EBV-transformed human lymphoid cells.